Climate Policy with Technology Transfers and Permit Trading - Carsten Helm; Stefan Pichler (University of Oldenburg, Department of Economics, 2011)
In this paper, we analyze technology transfers (TT) and tradable emission rights, which are core issues of the ongoing climate negotiations. Subsidizing TT leads to the adoption of better abatement technologies in developing countries, thereby reducing the international permit price. This is bene cial for industrialized countries as long as they are permit buyers, and as long as they can target subsidies to additional" investments. We also consider how TT affects countries' non-cooperative choices of permit endowments and nd that it reduces overall emissions. Finally, a simple numerical simulation model illustrates some results and explores some further comparative statics.
Keywords: D62; D78; H41; O38; Q58; 330; emissions trading; technology transfer; international climate policy.; Klimaschutz; Internationale Umweltpolitik; Technologietransfer; Subvention; Wirkungsanalyse; Emissionshandel; Nord-Süd-Beziehungen; Entwicklungsländer; Industrieländer